2019
DOI: 10.1158/1078-0432.ccr-19-1176
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Resistance Mutations to ALK Inhibitors Identified by Single Circulating Tumor Cell Sequencing inALK-Rearranged Non–Small-Cell Lung Cancer

Abstract: Purpose: Patients with anaplastic lymphoma kinase (ALK)-rearranged non-small-cell lung cancer (NSCLC) inevitably develop resistance to ALK inhibitors. New diagnostic strategies are needed to assess resistance mechanisms and provide patients with the most effective therapy. We asked whether single circulating tumor cell (CTC) sequencing can inform on resistance mutations to ALK inhibitors and underlying tumor heterogeneity in ALK-rearranged NSCLC. Experimental Design: Resistance mutations were investigated in C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 56 publications
1
88
0
Order By: Relevance
“…A number of studies have reported on the presence of ALK-translocated CTCs in blood taken from NSCLC patients [12,14,15,17,[21][22][23] with recent findings from Pailler et al, 2019, sequencing single CTCs that revealed the heterogeneity and resistance mutations in ALK-rearranged patients. The study by Pailler et al, 2019, demonstrated that various genes involved in the RTK-KRAS and TP53 pathways were found in patients with crizotinib resistance [24]. Therefore, the ability to assess the mutational changes in real time and over the course of therapy is of critical importance.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported on the presence of ALK-translocated CTCs in blood taken from NSCLC patients [12,14,15,17,[21][22][23] with recent findings from Pailler et al, 2019, sequencing single CTCs that revealed the heterogeneity and resistance mutations in ALK-rearranged patients. The study by Pailler et al, 2019, demonstrated that various genes involved in the RTK-KRAS and TP53 pathways were found in patients with crizotinib resistance [24]. Therefore, the ability to assess the mutational changes in real time and over the course of therapy is of critical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular characterization of CTCs has revealed that genomic changes of the tumor can be readily assessed via CTCs. This was recently highlighted by a number of studies identifying translocations/mutations in anaplastic lymphoma kinase (ALK) and EGFR in CTCs [ 74 , 75 , 76 , 77 , 78 ]. For EGFR mutations, the sensitivity of the assay increased with higher numbers of detected CTCs with concordance between EGFR mutation status in the tumor and CTC samples [ 77 ].…”
Section: Evolving Role Of Liquid Biopsy In Nsclcmentioning
confidence: 99%
“…A number of studies have reported the presence of ALK-translocated CTCs in blood from NSCLC patients [ 80 , 147 , 148 ]. Provencio et al, 2017, used CTCs for the dynamic monitoring of NSCLC patients with ALK rearrangement, as an example [ 80 ].…”
Section: Ctcs Information In Clinical Practicementioning
confidence: 99%
“…Provencio et al, 2017, used CTCs for the dynamic monitoring of NSCLC patients with ALK rearrangement, as an example [ 80 ]. Recently, Pailler et al (2019) demonstrated that many genes involved in the RTK- KRAS and TP53 pathways were found in patients with crizotinib resistance, showing the clinical utility of CTCs to identify therapeutic resistance mutations in ALK-rearranged patients and for treatment decisions [ 148 ].…”
Section: Ctcs Information In Clinical Practicementioning
confidence: 99%